2003
DOI: 10.1007/s00415-003-0995-2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral proton magnetic resonance spectroscopy in infantile Alexander disease

Abstract: Alexander disease (AD) is a rare genetic disorder of the central nervous system due to a dysfunction of astrocytes. The most common infantile form presents as a progressive leukodystrophy with macrocephalus. Recently, heterozygous de novo mutations in the gene encoding glial fibrillary acidic protein (GFAP) have been demonstrated to be associated with AD. We used localized proton magnetic resonance spectroscopy (MRS) to assess metabolic abnormalities in grey and white matter, basal ganglia, and cerebellum of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 41 publications
1
23
1
1
Order By: Relevance
“…21,30,32 Interestingly, this mechanism has been proposed in recent 1 H-MRSI studies to explain WM accumulation of Lac in different forms of leukodystrophies. 8,34 However, an impaired mitochondrial metabolism of the brain parenchyma cannot be definitely ruled out, although we did not observe morphological mitochondrial alterations in the peripheral nerve. Therefore, our 1 H-MRSI data, in agreement with pathological findings, suggest that brain WM degeneration in APBD may result from tissue damage involving both axons and myelin.…”
Section: Discussioncontrasting
confidence: 46%
“…21,30,32 Interestingly, this mechanism has been proposed in recent 1 H-MRSI studies to explain WM accumulation of Lac in different forms of leukodystrophies. 8,34 However, an impaired mitochondrial metabolism of the brain parenchyma cannot be definitely ruled out, although we did not observe morphological mitochondrial alterations in the peripheral nerve. Therefore, our 1 H-MRSI data, in agreement with pathological findings, suggest that brain WM degeneration in APBD may result from tissue damage involving both axons and myelin.…”
Section: Discussioncontrasting
confidence: 46%
“…A number of studies in mice and humans have found a correlation between astrocytosis and elevated C/C ratios (37)(38)(39)(40). Genetic disorders of astrocytes associated pathologically with astrocytosis displayed increased C/C ratios on MRS (38).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in mice and humans have found a correlation between astrocytosis and elevated C/C ratios (37)(38)(39)(40). Genetic disorders of astrocytes associated pathologically with astrocytosis displayed increased C/C ratios on MRS (38). The grade of malignant brain tumors is reflected in the content of astroglial elements relative to neurons and correlated with the C/C ratio in vivo (39) and in vitro (40).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, intracellular NAA reaches very high levels (Dezortova and Hajek 2008), yet this is not an indication of increased neuronal activity. On the other hand, in patients with Alexander disease, the signal of NAA is decreased (Brockmann et al 2003) to such an extent that, in one particular case, the NAA signal in the spectra of a child's brain cortex was absent altogether. The child was mentally impaired, but still she had some brain activity (Martin et al 2001).…”
Section: N-acetylaspartate and N-acetylaspartylglutamatementioning
confidence: 99%